Detection of Photosynthetic Performance of Stipa bungeana Seedlings under Climatic Change using Chlorophyll Fluorescence Imaging - Song, Xiliang; Zhou, Guangsheng; Xu, Zhenzhu; Lv, Xiaomin; Wang, Yuhui (Frontiers in Plant Science, 2016)
In this study, the impact of future climate change on photosynthetic efficiency as well as energy partitioning in the Stipa bungeana was investigated by using chlorophyll fluorescence imaging (CFI) technique. Two thermal regimes (room temperature, T0: 23.0/17.0°C; High temperature, T6: 29.0/23.0°C) and three water conditions (Control, W0; Water deficit, W−30; excess precipitation, W+30) were set up in artificial control chambers. The results showed that excess precipitation had no significant effect on chlorophyll fluorescence parameters, while water deficit decreased the maximal quantum yield of photosystem II (PSII) photochemistry for the dark-adapted state (Fv/Fm) by 16.7%, with no large change in maximal quantum yield of PSII photochemistry for the light-adapted state (FV′/FM′) and coefficient of the photochemical quenching (qP) at T0 condition. Under T6 condition, high temperature offset the negative effect of water deficit on Fv/Fm and enhanced the positive effect of excess precipitation on Fv/Fm, Fv′/Fm′, and qP, the values of which all increased. This indicates that the temperature higher by 6°C will be beneficial to the photosynthetic performance of S. bungeana. Spatial changes of photosynthetic performance were monitored in three areas of interest (AOIs) located on the bottom, middle and upper position of leaf. Chlorophyll fluorescence images (Fv/Fm, actual quantum yield of PSII photochemistry for the light-adapted state (ΦPSII), quantum yield of non-regulated energy dissipation for the light-adapted state (ΦNO) at T0 condition, and ΦPSII at T6 condition) showed a large spatial variation, with greater value of ΦNO and lower values of Fv/Fm and ΦPSII in the upper position of leaves. Moreover, there was a closer relationship between ΦPSII and ΦNO, suggesting that the energy dissipation by non-regulated quenching mechanisms played a dominant role in the yield of PSII photochemistry. It was also found that, among all measured fluorescence parameters, the Fv/Fm ratio was most sensitive to precipitation change at T0, while ΦPSII was the most sensitive indicator at T6.